Study of Refractive Index, Density, Molar Volume and Their Excess Properties of Binary Systems - Kamble, S.P.; Undre, P.B.; Sudake, Y.S.; Maharolkar, A.P.; Khirade, P.W. (Asian Journal of Chemistry, 2012)
Refractive index and density have been measured over the whole composition range for (dimethyl sulphoxide, dimethyl acetamide, 2-propanol(2-P), glycerol (GL), 2-methoxymethanol(2-ME) and 2-ethoxyethanol(2-EE)) at 293 K along with the properties of the pure component. Excess density, excess refractive index and molar volume for the binary system at above mentioned temperature were calculated and fitted to Redlich-Kister equation to determine aj coefficient. And the deviation of the excess properties from the ideal values suggests that there may be the hydrogen bonding and dispersion intermolecular interactions in the system under study.